Legitimasi Kedudukan Kepala Desa dalam Penyelesaian Sengketa Agraria - Dewi, Sri Anggraini Kusuma; Hasibuan, Rezky Panji Perdana Martua (University of Jember, Indonesia, 2021)
The agrarian disputes often occur in rural areas, considering that the majority of the livelihoods of rural communities are farmers. In this regard, rural communities also cannot be avoided from agrarian conflicts that occur between residents, including in terms of inheritance. This social legal research aims to analyze the factors causing the occurrence of agrarian conflicts in rural areas; and explain the role of the village head in dealing with disputes related to land. This empirical legal research uses a qualitative approach that is based on primary data and secondary data as obtained through a series of observations, interviews, and documentation. The results of the study indicate that rural communities tend to choose the head of village as the party that resolves agrarian disputes in rural areas. Therefore, the rural community perspective believes and considers the head of village to be able to provide a sense of community justice. The scheme used by the head of village is mediation or what is often called 'deliberation for consensus'. KEYWORDS: Land, Customary Law, Head of Village, Amadanom, Malang.